Unwoven fabric laminate and membrane separation active sludge treatment device
A nonwoven fabric laminate with a sulfonic acid group-containing polymer layer addresses biofouling issues in membrane separation activated sludge methods, enhancing membrane performance and reducing fouling.
Patent Information
- Application Number
- JP2023100283
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
Existing nonwoven fabrics used in membrane separation activated sludge methods face issues with biofouling, leading to decreased membrane filtration flow rates, and current solutions like tetrafluoroethylene resins are expensive and have processability limitations.
A nonwoven fabric laminate is developed with a base layer of nonwoven fabric and a laminated layer of a polymer containing sulfonic acid groups, which suppresses biofouling and is cost-effective.
The laminate exhibits high biofouling suppression and maintains a high water permeation flux, reducing membrane fouling and extending the membrane's operational lifespan.
Smart Images

Figure 2025000432000018 
Figure 2025000432000019 
Figure 2025000432000020
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonwoven fabric laminate and a membrane separation activated sludge treatment apparatus. [Background technology]
[0002] Nonwoven fabrics are easy to mass-produce and the surface area, air permeability, etc. can be easily controlled by the manufacturing method, so they are used in many applications, such as various medical and industrial filters, sanitary materials such as masks and disposable diapers, etc. In addition, because they can be manufactured using a variety of resins as raw materials, the properties derived from the raw resins can be reflected in the nonwoven fabric.
[0003] Nonwoven fabrics are used, for example, in biological treatment methods in the field of wastewater treatment, more specifically, as membranes in the membrane separation activated sludge process, which is a type of activated sludge process. As such membranes, flat membranes such as ceramic membranes and nonwoven fabrics, as well as hollow fiber membranes, are used. However, in any case, degradation of membrane performance (such as a decrease in membrane filtration flow rate) due to biofouling, etc., can be a problem.
[0004] As a method for solving the above problems, Patent Document 1 discloses a method in which one of the features is to use a tetrafluoroethylene resin porous body as a separation membrane. Patent Document 2 discloses a method for suppressing a decrease in membrane filtration flow rate by using particles with hydrophilized surfaces and specific uneven shapes as a membrane cleaning agent.
[0005] Patent Document 3 discloses a method for suppressing fouling by controlling the transmembrane pressure difference. On the other hand, there are reports that resins having sulfonic acid groups are effective as resins with less biofouling (eg, Non-Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2010-253355 A [Patent Document 2] JP 2005-74357 A [Patent Document 3] International Publication No. 2011 / 048681 [Non-patent literature]
[0007] [Non-Patent Document 1] Membrane, 39, 209 (2014) [Non-Patent Document 2] Journal of Environmental Biotechnology,14,131(2015) Summary of the Invention [Problem to be solved by the invention]
[0008] It is generally believed that various factors are involved in the occurrence of biofouling, but there are few reports on suppressing biofouling by membrane structure. The tetrafluoroethylene resin disclosed in Patent Document 1 is a special resin, which is relatively expensive and is said to have limitations in processability. The resin disclosed in Non-Patent Document 1 is also a special engineering plastic, and the resin disclosed in Non-Patent Document 2 is a polyethylene modified to introduce sulfonic acid groups.
[0009] Therefore, an object of the present invention is to provide a material that has a high biofouling suppression effect and can be produced at low cost. [Means for solving the problem]
[0010] As a result of the inventor's investigations, it is proposed that a laminate in which a polymer having sulfonic acid groups is laminated by a method such as coating onto a nonwoven fabric, which is considered to be a relatively inexpensive material, can be a material that can solve the above problems. Examples of the aspects of the present invention are shown below.
[0011] [1] A substrate layer (LA) containing a nonwoven fabric (A) and a layer (LB) containing a polymer (B) having a sulfonic acid group structure, A nonwoven fabric laminate having the above-mentioned (LA) / (LB) structure, which has air permeability.
[0012] [2] The nonwoven fabric laminate according to [1], wherein the polymer (B) is a polymer having a structural unit (1) represented by the following formula (1) and a structural unit (2) represented by the following formula (2):
[0013] [ka]
[0014] [In formulas (1) and (2), R 1 ~R 10 are each independently H, Cl, F, or CF 3 or C m H 2m+1 (m represents an integer of 1 to 10), R 1 ~R 10 may be present in two or more aromatic rings, and C m H 2m+1 If there are two or more C m H 2m+1 may be the same or different from each other. X 1 ~X 5 are each independently H, Cl, F, or CF 3 or a sulfonic acid group, X 1 ~X 5 at least one of the groups is a sulfonic acid group; X 1 ~X 5 may be present in two or more on an aromatic ring, and when two or more sulfonic acid groups are present on one aromatic ring, the respective sulfonic acid groups may be the same or different. A 1 ~A 6 each independently represents a direct bond, -CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 )2 -, -O- or -CO-. i, j, k and l each independently represent 0 or 1.
[0015] [3] The nonwoven fabric laminate according to [2], wherein in the entire polymer (B), the molar fraction of the structural unit (1) relative to the total amount of the structural unit (1) and the structural unit (2) is 0.1 to 0.9.
[0016] [4] The nonwoven fabric laminate according to [1], wherein the polymer (B) has a weight average molecular weight (Mw) of 70,000 to 200,000. [5] The nonwoven fabric laminate according to [1], wherein the polymer (B) has a sulfonic acid group equivalent of 200 to 5,000 g / mol.
[0017] [6] Water permeation flux (L / (m 2 The nonwoven fabric laminate according to [1], wherein LMH) is 100 to 100,000.
[0018] [7] A method for producing the nonwoven fabric laminate according to any one of the above [1] to [6], comprising the steps of applying a polymer (B) having a sulfonic acid group structure to at least one surface of a base layer (LA) comprising a nonwoven fabric (A), and drying the applied polymer (B).
[0019] [8] A membrane separation activated sludge treatment device, in which the nonwoven fabric laminate according to any one of [1] to [6] is immersed in a treatment water tank into which activated sludge containing microorganisms has been charged. Effect of the Invention
[0020] According to the present invention, by using a nonwoven fabric, even a polymer having a strong acid structure such as a sulfonic acid group can be made into a strong laminate. Since the nonwoven fabric laminate of the present invention is a laminate having a nonwoven fabric as a base layer, it is expected to have a high biofouling suppression effect and be a relatively inexpensive membrane. [Brief description of the drawings]
[0021] [Figure 1] 1 is an electron microscope photograph of the coated surface of the nonwoven fabric laminate of Example 5 of the present application. [Diagram 2] 1 is an electron microscope photograph of a cross section of the nonwoven fabric laminate of Example 5 of the present application. [Diagram 3] FIG. 1 is a schematic diagram of a water permeation flux measuring device used in the examples of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described in detail below. [Nonwoven fabric (A)] As the nonwoven fabric used in the nonwoven fabric laminate of the present invention, any known nonwoven fabric can be used without any restrictions. For example, natural pulp and synthetic pulp can be used without distinction. More specifically, examples of the raw resin of the nonwoven fabric include polymers containing heteroatoms such as cellulose, polyester, acrylic resin, and halogen-containing hydrocarbon polymers such as polyvinylidene fluoride, and nonwoven fabrics using hydrocarbon polymers such as polyolefins such as ethylene polymers, propylene polymers, butene polymers, and 4-methyl-1-butene polymers, and polystyrene. Since the above-mentioned resins usually tend to have poor compatibility with the polymer (B) having a sulfonic acid group described later, it is considered difficult to make a laminate. In particular, the above-mentioned hydrocarbon polymers tend to have poor polarity, and this tendency is said to be remarkable. On the other hand, it can be considered that the degree of polarity of these nonwoven fabrics can be easily controlled over a wide range by using a known polarizing method such as corona treatment due to their large surface area. In addition, since the fibers of the nonwoven fabric are relatively fine, the polymer (B) may easily assume a structure surrounding the nonwoven fabric fibers, forming a strong laminate structure that is difficult to peel off.
[0023] The fiber diameter of the nonwoven fabric of the present invention is not particularly limited, but from the above viewpoints, it is preferably 0.05 to 100 micrometers (μm). A more preferable lower limit is 0.1 μm, even more preferably 0.2 μm, and particularly preferably 0.3 μm. On the other hand, a more preferable upper limit is 80 μm, even more preferably 60 μm, and particularly preferably 50 μm.
[0024] The thickness of the nonwoven fabric as a web is not particularly limited because it can be freely controlled by stacking the nonwoven fabrics themselves. On the other hand, the preferred thickness of the nonwoven fabric as a basic unit in consideration of production efficiency is 50 μm to 50 mm. The more preferred lower limit is 60 μm, even more preferably 70 μm, and particularly preferably 80 μm. The more preferred upper limit is 40 mm, even more preferably 30 mm, particularly preferably 20 mm, and especially preferably 10 mm.
[0025] The method for producing the nonwoven fabric is not particularly limited. Any known method can be used. The method for producing the polyethylene or polypropylene nonwoven fabric includes a spunbond method, a meltblown method, and the like.
[0026] As the nonwoven fabric (A) of the present invention, polyolefin nonwoven fabrics are preferred, particularly polyethylene nonwoven fabrics and polypropylene nonwoven fabrics, in consideration of the cost, ease of mass production, ease of adjusting physical properties, etc. Natural pulp is also a suitable example.
[0027] [Polymer (B) having sulfonic acid groups] The polymer (B) having a sulfonic acid group used in the nonwoven fabric laminate of the present invention is not particularly limited, but is preferably a polymer having a rigid structure. Examples of the rigid structure include those having a basic skeleton of so-called engineering plastics such as aromatic polyether structure, aromatic polyether ketone, and aromatic polyamide. If the polymer has such a structure, it will be a strong structure when laminated with the nonwoven fabric as described above, and since its molecular mobility is expected to be low, it is expected that it will not easily form a structure that fills the gaps between the transitions of the nonwoven fabric.
[0028] From the above viewpoint, an aromatic polyether resin (BK) (hereinafter also referred to as "resin (BK)") having structural units of the following formula (1) and formula (2) is considered to be suitable.
[0029] [ka]
[0030] In formulas (1) and (2), i, j, k and l each independently represent 0 or 1. R 1 ~R 10 are each independently H, Cl, F, or CF 3 or C m H 2m+1 (m is an integer from 1 to 10), m H 2m+1 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group.
[0031] The above R 1 ~R 10 At least one of the following is C m H 2m+1 (m is an integer of 1 to 10). Specifically, i, j, k, and l, and R 1 ~R 10 The structural unit (1) and / or the structural unit (2) are C m H 2m+1 That is, when i, j, k, and l are all 1, R 1 ~R 10 At least one of the following is C m H 2m+1 For example, if i = 0, j = 1, k = 0 and l = 1, then R 1 ~R 3 , R 5 ~R 8 and R 10 At least one of the following is C m H 2m+1 It is.
[0032] R 1 ~R 10 may be present in two or more aromatic rings, and C m H 2m+1 If there are two or more C m H2m+1 may be the same or different from each other. X 1 ~X 5 are each independently H, Cl, F, or CF 3 Or a sulfonic acid group.
[0033] In formulas (1) and (2), X 1 ~X 5 At least one of i and j and X is a sulfonic acid group. 1 ~X 5 is selected so that the structural unit (1) has at least one sulfonic acid group. That is, when i=1 and j=1, X 1 ~X 5 At least one of the groups is a sulfonic acid group, but when j=0, X 1 ~X 3 At least one of is a sulfonic acid group, and when i=0 and j=1, X 1 ~X 3 and X 5 At least one of the groups is a sulfonic acid group.
[0034] X 1 ~X 5 may be present in two or more on an aromatic ring, and when two or more sulfonic acid groups are present on one aromatic ring, the respective sulfonic acid groups may be the same or different.
[0035] In formulas (1) and (2), A 1 ~A 6 each independently represents a direct bond, -CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, -O- or -CO-, and A 1 ~A 6 At least one of the is preferably -CO-. The lines at both ends of formulas (1) and (2) indicate bonds between adjacent structural units.
[0036] In the present invention, the sulfonic acid group means a functional group which easily releases a proton or a group in which a hydrogen atom of the functional group is substituted with Na or K. Examples of the sulfonic acid group include a sulfonic acid group (-SO 3 H), carboxylic acid group (-COOH), phosphonic acid group (-PO 3 H 2 ), alkylsulfonic acid group (-(CH 2 ) n SO 3 H), alkyl carboxylic acid group (-(CH 2 ) n COOH), alkylphosphonic acid group (-(CH 2 ) n PO 3 H 2 ), hydroxyphenyl group (-C 6 H 4 OH) and those in which the terminal hydrogen atom is substituted with Na or K. n is an integer of 1 to 10. The sulfonic acid group includes, for example, -C n' H 2n' -SO 3 Y (n' is an integer of 0 to 10, preferably 0, and Y is H, Na or K) is preferred.
[0037] Examples of the structural unit (1) include structural units represented by the following formula (1-1) or (1-2). In these structures, A 1 is preferably -CO-,
[0038] [ka]
[0039] More specifically, the structural unit may be represented by the following formula (1-3) or (1-4).
[0040] [ka] (In the formula, each Z is independently the sulfonic acid group, each s is independently an integer of 0 to 3, each t is independently an integer of 0 to 4, and the lines at both ends represent bonds to adjacent structural units. The other symbols are as defined above.)
[0041] Examples of the structural unit (2) include structural units represented by the following formula (2-1) or (2-2):
[0042] [ka]
[0043] More specifically, the structural unit may be represented by the following formula (2-3) or (2-4).
[0044] [ka] (In the formula, each t is independently an integer of 0 to 4, and the lines at both ends indicate bonds to adjacent structural units. The symbols other than t are defined as above.) Of course, the present invention also includes an embodiment where m=0 in the above formula.
[0045] In the entire resin (BK), the molar fraction of the structural unit (1) relative to the total amount of the structural unit (1) and the structural unit (2) is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.25 or more, and is preferably 0.9 or less, more preferably 0.7 or less, even more preferably 0.6 or less. The above numerical ranges can be appropriately adjusted depending on the type of nonwoven fabric (A) used.
[0046] The resin (BK) may further contain a structural unit derived from a polyfunctional compound described later. The resin (BK) may be crosslinked or non-crosslinked. The resin (BK) may also contain other components in a small amount (for example, 1% by mass or less, or 0.1% by mass or less) that does not impair the effects of the present invention.
[0047] The weight average molecular weight (Mw) of the resin (BK), measured by GPC (Gel Permeation Chromatography) under the following conditions (1) to (6), is preferably 70,000 or more, more preferably 80,000 or more, and even more preferably 90,000 or more. When the molecular weight is within the above range, the resulting semipermeable membrane has high mechanical properties and is less likely to break during membrane formation or use. In addition, from the viewpoint of gel generation rate, the weight average molecular weight is preferably 200,000 or less, more preferably 180,000 or less.
[0048] (1) Measurement temperature: 40℃ (2) Developing solvent: N,N-dimethylformamide (DMF) (3) Flow rate: 1.0ml / min (4) Injection volume: 500μl (5) Detector: UV detector (6) Molecular weight standard: Standard polystyrene The weight average molecular weight can be controlled by adjusting the molar ratio of raw material monomers and the amount of end-capping agent when producing the resin (BK).
[0049] The sulfonic acid group equivalent of the resin (BK), i.e., the mass of the resin (BK) per mole of sulfonic acid group, is preferably 200 g / mol or more, and more preferably 5000 g / mol or less, more preferably 1000 g / mol or less, since a semipermeable membrane having a large water permeation flux and high economical properties can be obtained.
[0050] (Manufacturing method of resin (BK)) Hereinafter, a method for producing the above-mentioned resin (BK) having a rigid structure will be described as a representative example of the polymer (B).
[0051] The above resin (BK) can be obtained by condensation of monomers having an aromatic ring according to a conventionally known method (for example, the method described in WO 2003 / 33566). For example, the following formulae (1a) and (2a) can be used:
[0052] [ka] and a monomer having a halogen substituent represented by the following formulae (1b) and (2b):
[0053] [ka] The resin can be obtained by condensation polymerization with a monomer having a hydroxyl group represented by the following formula:
[0054] In the formula, Y is a halogen atom, and the meanings of the other symbols are the same as those of the same symbols used in the above formulas (1) and (2). The halogen atoms preferably include fluorine and chlorine.
[0055] K for condensation 2 CO 3 It is preferable to use a basic catalyst such as The monomer represented by the above formula (1a) (wherein X 1 ~X 2 at least one of which is a sulfonic acid group. Examples of the sulfonic acid group-containing aromatic dihalide compounds include 5,5'-carbonylbis(sodium 2-fluorobenzenesulfonate) and 5,5'-carbonylbis(sodium 2-chlorobenzenesulfonate).
[0056] Examples of the monomer represented by the above formula (2a) include: Aromatic dihalide compounds such as 4,4'-difluorobenzophenone, 3,3'-difluorobenzophenone, 4,4'-dichlorobenzophenone, 3,3'-dichlorobenzophenone, 4,4'-difluorobiphenyl, 4,4'-difluorodiphenylmethane, 4,4'-dichlorodiphenylmethane, and 4,4'-difluorodiphenyl ether; and Examples of the aromatic dihalide compounds having an alkyl group include 3,3'-dimethyl-4,4'-difluorobenzophenone, 3,3'-diethyl-4,4'-difluorobenzophenone, 3,3',5,5'-tetramethyl-4,4'-difluorobenzophenone, 3,3'-dimethyl-4,4'-dichlorobenzophenone, and 3,3',4,4'-tetramethyl-5,5'-dichlorobenzophenone.
[0057] The monomer represented by the above formula (2b) (or the monomer represented by the above formula (1b) (wherein X 3 ~X 5 are all hydrogen atoms. Aromatic dihydroxy compounds such as 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 2,2-bis(4-hydroxyphenyl)propane, 1,1,1,3,3,3-hexafluoro-2,2-bis(4-hydroxyphenyl)propane, 1,4-bis(4-hydroxyphenyl)benzene, α,α'-bis(4-hydroxyphenyl)-1,4-dimethylbenzene, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, α,α'-bis(4-hydroxyphenyl)-1,3-diisopropylbenzene, 1,4-bis(4-hydroxybenzoyl)benzene, and 3,3'-difluoro-4,4'-dihydroxybiphenyl; and 3,3'-Dimethyl-4,4'-dihydroxybiphenyl, 3,3',5,5'-tetramethyl-4,4'-dihydroxybiphenyl, 3,3'-Dimethyl-4,4'-dihydroxydiphenylmethane, 3,3',5,5'-Tetramethyl-4,4'-dihydroxydiphenylmethane (also known as bis(3,5-dimethyl-4-hydroxyphenyl)methane), 3,3',5,5'-tetraethyl-4,4'-dihydroxydiphenylmethane, 3,3'-Dimethyl-4,4'-dihydroxydiphenyl ether, 3,3',5,5'-Tetramethyl-4,4'-dihydroxydiphenyl ether, 2,2-Bis(3-methyl-4-hydroxydiphenyl ether), Examples of alkyl group-containing aromatic dihydroxy compounds include 2,2-bis(3-ethyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, α,α'-bis(3-methyl-4-hydroxyphenyl)-1,4-diisopropylbenzene, α,α'-bis(3,5-dimethyl-4-hydroxyphenyl)-1,4-diisopropylbenzene, α,α'-bis(3-methyl-4-hydroxyphenyl)-1,3-diisopropylbenzene, and α,α'-bis(3,5-dimethyl-4-hydroxyphenyl)-1,3-diisopropylbenzene.
[0058] A polyfunctional compound may be copolymerized with the monomer as long as the solvent solubility of the resin (BK) is not impaired. By copolymerizing a polyfunctional compound, the resin (BK) can have a micro-crosslinked structure. Examples of polyfunctional compounds include those having three or more hydroxyl groups in one molecule, such as (2,4-dihydroxyphenyl)(4-hydroxyphenyl)methanone, 4-[1-(4-hydroxyphenyl)-1-methylethyl]-1,3-benzenediol, 4-[(2,3,5-trimethyl-4-hydroxyphenyl)methyl]-1,3-benzenediol, 4-[(4-hydroxyphenyl)methyl]-1,2,3-benzenetriol, (4-hydroxyphenyl)(2,3,4-trihydroxyphenyl)methanone, 4-[(3,5-dimethyl- Examples of such benzenediols include 4,4'-[1,4-phenylenebis(1-methylethylidene)]bis[benzene-1,2-diol], 5,5'-[1,4-phenylenebis(1-methylethylidene)]bis[benzene-1,2,3-triol], α,α,α'-tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene, phloroglucin, and pyrogallol.
[0059] From the viewpoint of preventing a decrease in the solvent solubility of the resin (BK), a decrease in the fluidity of the resin during membrane formation, and a decrease in the elongation rate of the semipermeable membrane, the amount of these copolymerizations is preferably 0 to 8 mol% / total OH equivalent (i.e., of the total amount (100 mol%) of OH groups possessed by the monomer of formula (1b), the monomer of formula (2b), and the polyfunctional monomer, 0 to 8 mol% are OH groups derived from the polyfunctional monomer), and more preferably 0 to 5 mol% / total OH equivalent.
[0060] (Varnish of polymer (B)) The polymer (B) of the present invention has a molecular structure that is basically linear, and even if it has a crosslinked structure derived from the polyfunctional compound, the amount of the crosslinked structure is preferably small. Such a resin tends to have excellent solvent solubility, and can be in the form of a varnish dissolved in a resin solvent. It is also obvious that such a varnish is suitable for coating on a nonwoven fabric, which will be described later.
[0061] Examples of the solvent are not particularly limited as long as they are suitable for the sulfonic acid group-containing polymer, and include water, alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as methyl chloride and methylene chloride, ethers such as dichloroethyl ether, 1,4-dioxane, and tetrahydrofuran, fatty acid esters such as methyl acetate and ethyl acetate, ketones such as acetone and methyl ethyl ketone, cellosolves such as 2-methoxyethanol and 2-ethoxyethanol, and aprotic polar solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, and dimethyl carbonate. These can be used alone or in combination of two or more. (Water is not used alone as a solvent in principle.) Among them, lower alcohols (methanol, ethanol, 1-propanol, 2-propanol, t-butyl alcohol, etc.), tetrahydrofuran, N,N-dimethylformamide, N-methyl-2-pyrrolidone, etc. are preferred because of their water solubility, and mixed solvents of these with water are also preferred. The resin concentration in the varnish can be selected depending on the method of using the varnish, but is preferably 1% by mass or more and 80% by mass or less.
[0062] Such a varnish can be suitably used as a coating material in the method for forming a laminate with the nonwoven fabric (A) as described below.
[0063] [Method for producing a nonwoven fabric laminate having a laminated structure of a substrate layer (LA) containing a nonwoven fabric (A) / a layer (LB) containing a polymer (B)] The method for producing a nonwoven fabric laminate having a laminated structure of a base layer (LA) containing the nonwoven fabric (A) / a layer (LB) containing the polymer (B) can be any known method without limitation. A preferred example is a coating method in which a varnish of the polymer (B) is applied to the nonwoven fabric (A). That is, the method for producing a nonwoven fabric laminate according to the present invention includes a step of applying a polymer (B) having a sulfonic acid group structure to at least one surface of the base layer (LA) containing the nonwoven fabric (A) and drying the applied polymer. Hereinafter, a method using a resin (BK) suitable for the present invention will be introduced as an example.
[0064] The coating method is a method in which the varnish is applied onto the nonwoven fabric (A) and the solvent is removed by volatilization to obtain a laminate. If the organic solvent of the varnish remains in the laminate, the laminate structure may be easily damaged, and therefore, in the coating method, it is preferable to perform sufficient drying and / or washing with water, an aqueous sulfuric acid solution, hydrochloric acid, or the like.
[0065] The nonwoven fabric laminate of the present invention obtainable by the above-mentioned method is characterized by having air permeability since it is a laminate using a nonwoven fabric as a substrate. The fact that the laminate of the present invention has air permeability can be confirmed by a known method for measuring air permeability, particularly a method for measuring the air permeability of nonwoven fabric. A specific example of such a method is the method for measuring Gurley air permeability.
[0066] The nonwoven fabric laminate of the present invention obtainable by the above-mentioned method has a water permeation flux (L / (m 2 ·h) (LMH)) is preferably 100 to 100,000. A more preferable lower limit is 200, even more preferably 500, and particularly preferably 1,000. A more preferable upper limit is 80,000, even more preferably 50,000, and particularly preferably 10,000.
[0067] In addition, when the sulfonic acid group of the resin (BK) used to produce the laminate is a functional group that easily releases protons, in which a hydrogen atom is substituted with Na or K, a laminate of the nonwoven fabric (A) and the aromatic polyether resin (BK) may be formed, and then the resulting film may be contacted with an aqueous solution of hydrochloric acid, sulfuric acid, or the like, to substitute the Na or K of the sulfonic acid group with a hydrogen atom.
[0068] [Nonwoven fabric laminate] As described above, the nonwoven fabric laminate of the present invention has a substrate layer (LA) containing a nonwoven fabric (A) and a layer (LB) containing a polymer (B).
[0069] The substrate layer (LA) is a layer that does not substantially have sulfonic acid groups, and more specifically, the content of sulfonic acid groups in the layer (LB) is preferably 50% or less, more preferably 30% or less, even more preferably 10% or less, and particularly preferably 5% or less. The preferred lower limit is of course zero, and it is preferable that sulfur is substantially undetectable in the measurement by the EDS method described later.
[0070] The layer (LB) is not particularly limited as long as it contains the polymer (B), but in the present invention, an embodiment containing a nonwoven fabric (A) and a polymer (B) is particularly preferred, and an embodiment in which the polymer (B) is attached to the fibers of the nonwoven fabric (A) is more preferred. Furthermore, an embodiment in which the polymer (B) covers the circumference of the fibers of the nonwoven fabric (A) is also preferred. In such an embodiment, even if the affinity between the fibers of the nonwoven fabric (A) and the polymer (B) is low, the polymer (B) is unlikely to peel off from the nonwoven fabric (A), and a layer (LB) that is stable over time can be formed.
[0071] The thickness of the base layer (LA) of the nonwoven fabric laminate of the present invention is 10 to 95% of the entire laminate. The more preferred lower limit is 30%, even more preferred 50%, and particularly preferred 60%. On the other hand, the more preferred upper limit is 90%, even more preferred 80%, and particularly preferred 75%. (The total thickness of the base layer (LA) and the layer (LB) is taken as 100%). Such an embodiment is preferably obtained by a method of coating the nonwoven fabric (A) with a varnish of the polymer (B).
[0072] [Uses of the laminate] The laminate of the present invention can be used, for example, as a membrane for separating floating flocs that are generated when aerobic or anaerobic bacteria decompose organic matter in wastewater and grow during wastewater treatment by an activated sludge process, thereby obtaining water with a reduced organic matter content as filtrate.
[0073] In this case, if the buoyant flocs accumulate on the membrane, the bacteria may grow on the membrane and cause biofouling. However, since the laminate of the present invention has a layer (LB) containing a polymer (B) having a sulfonic acid group formed on its surface, if the side on which the layer (LB) is formed is installed on the wastewater purification tank side, biofouling is unlikely to occur on the membrane, and the frequency of replacement of the separation membrane can be reduced.
[0074] The nonwoven fabric laminate of the present invention has a structure in which the polymer (B) is contained in only a part of the entire laminate, preferably in an embodiment in which the polymer (B) is attached to the surface of a part of the nonwoven fabric fibers, and the proportion of the polymer containing sulfonic acid groups is relatively small, but surprisingly, it tends to exhibit a sufficient biofouling effect. The inventors believe that this is because the polymer containing sulfonic acid groups has the effect of, for example, aggregating bacteria and inhibiting bacterial growth, and prevents the bacteria from eroding into the laminate. For this reason, since substantially only the surface of the layer (LB) in the laminate is the site related to biofouling, it is speculated that even an embodiment of a laminate including a layer substantially free of sulfonic acid groups as in the present invention will exhibit a sufficient biofouling effect.
[0075] In addition, the resin can be used in applications suitable for resins having sulfonic acid groups, such as ion exchange membranes.
[0076] In the membrane bioreactor according to the present invention, the nonwoven fabric laminate of the present invention is immersed in a treatment water tank into which activated sludge containing microorganisms has been put. Other configurations of the membrane bioreactor are not particularly limited, and known configurations can be adopted. EXAMPLES
[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. The abbreviations used in the present examples and comparative examples are as follows.
[0078] (1) Solvent DMSO: Dimethyl sulfoxide DMF: N,N-dimethylformamide (2) Components of aromatic polyether DFBP: 4,4'-difluorobenzophenone DSDFBP: 5,5'-carbonylbis(sodium 2-fluorobenzenesulfonate)
[0079] [ka]
[0080] TMBPF: 3,3',5,5'-tetramethyl-4,4'-dihydroxydiphenylmethane DSDCDPS: 5,5'-sulfonylbis(sodium 2-chlorobenzenesulfonate)
[0081] [ka]
[0082] SEM image measurement SEM photographs of the nonwoven fabric laminate were taken in a conventional manner using the following equipment. Manufacturer: JEOL Ltd. Model name: JSM-6380
[0083] SEM-EDS image measurement The nonwoven fabric laminate was sliced at a cutting edge to expose its cross section, and the cross section was photographed in the usual manner and the sulfur atom content and sodium atom content of the coated layer (layer-A) and uncoated layer (layer-B) were measured using SEM-EDS. Scanning electron microscope (SEM) equipment Manufacturer: Hitachi High-Technologies Corporation Model name: Scanning electron microscope (S-4800) Energy dispersive X-ray analyzer (EDS) Manufacturer: Bruker AXS Model name:QUANTAX FlatQUAD
[0084] Water permeation flux measurement The water permeation flux was measured using an apparatus that can be represented in FIG. The apparatus includes a feed solution tank 1, a flow path 2, a pump 3, a draw solution tank 11, a flow path 12, a pump 13, and an evaluation cell 21. The feed solution tank 1 is placed on a balance 4. At the start of the evaluation, 500 g of Milli-Q water having an electrical conductivity of 50 μS / cm or less is stored as a feed solution FS (Feed Solution) in the feed solution tank 1, and 500 g of Milli-Q water is also stored in the draw solution tank 11. The feed solution in the feed solution tank 1 flows through the flow path 2 by using the pump 3, and the draw solution in the draw solution tank 11 flows through the flow path 12 by using the pump 13. The feed solution flowing through the flow path 2 and the draw solution flowing through the flow path 12 are in contact with each other through the nonwoven fabric laminate sample 22 inside the evaluation cell 21, and the water flow rate is adjusted by each pump so that a water pressure of 0.1 MPa is applied from the flow path 2 to the flow path 12 through the sample 22, and a part of the water in the feed solution moves to the draw solution side. The amount of water transferred at this time was measured as the amount of weight loss using the balance 4. The water permeation flux (Jw) was determined by the following method. The amount of weight loss of the feed solution was measured every minute using the balance 4, and the amount of weight loss per unit time and unit area of the sample 22 was determined as the water permeation flux (L / (m 2 ·h)(LMH)).
[0085] Fouling resistance evaluation (protein adsorption test) A protein adsorption test was performed using a general protein quantification method based on ultraviolet light absorption. A 4 cm2 coated surface was placed in 20 mL of albumin solution. 2 A nonwoven fabric laminate sample was left in the immersed state. After one hour, the ultraviolet light absorption spectrum of the immersion liquid was measured using a UV-visible spectrophotometer. The albumin concentration of the immersion liquid was calculated from the spectral intensity. The smaller this value is, the easier it is for proteins such as activated sludge bacteria to adhere to the nonwoven fabric laminate, i.e., it is an index suggesting the ease with which fouling occurs.
[0086] (Resin synthesis example 1) In a five-necked reactor equipped with a nitrogen inlet tube, a thermometer, a reflux condenser, and a stirrer, 40.1 g (0.095 mol) of DSDFBP, 62.2 g (0.285 mol) of DFBP, 97.4 g (0.380 mol) of TMBPF, and 65.7 g (0.475 mol) of potassium carbonate obtained by the method described in Synthesis Example 1 of JP-A-2014-533 were weighed out. 783.4 g of DMSO and 261.1 g of toluene were added thereto, stirred under a nitrogen atmosphere, heated at 130° C. for 12 hours, and the generated water was removed from the system, and then the toluene was distilled off.
[0087] The reaction was continued at 160°C for 12 hours to obtain a viscous polymer solution. The obtained solution was diluted with 570g of toluene and then poured into 2400g of methanol. The precipitated polymer powder was filtered, washed, and then dried at 150°C for 4 hours to obtain 171.6g of polyetherketone powder (95% yield) (Resin 1).
[0088] Resin 1 has the structural unit (1)
[0089] [ka] As the structural unit (2), 25 mol % of the structure (sulfonic acid unit) represented by the following formula:
[0090] [ka] The results are shown in Table 1.
[0091] (Resin synthesis example 2) The resin raw materials and solvent were 48.1 g (0.114 mol) of DSDFBP, 58.0 g (0.265 mol) of DFBP, 97.4 g (0.380 mol) of TMBPF, 65.7 g (0.475 mol) of potassium carbonate, 814.4 g of DMSO, and 271.5 g of toluene, but the procedure was the same as in Example 1 to obtain 175.2 g of polymer powder (93% yield) (Resin 2). The results are shown in Table 1.
[0092] (Resin synthesis example 3) The resin raw materials and solvent were 64.2 g (0.152 mol) of DSDFBP, 49.8 g (0.228 mol) of DFBP, 97.4 g (0.380 mol) of TMBPF, 65.7 g (0.475 mol) of potassium carbonate, 845.4 g of DMSO, and 281.8 g of toluene, and the same procedure as in Resin Synthesis Example 1 was followed to obtain 168.7 g of polymer powder (86% yield) (Resin 3). The results are shown in Table 1.
[0093] (Resin synthesis example 4) The resin raw materials and solvent were 80.2 g (0.190 mol) of DSDFBP, 41.5 g (0.190 mol) of DFBP, 97.4 g (0.380 mol) of TMBPF, 65.7 g (0.475 mol) of potassium carbonate, 876.4 g of DMSO, and 292.1 g of toluene, and the same procedure as in Resin Synthesis Example 1 was followed to obtain 174.6 g of polymer powder (86% yield) (Resin 4). The results are shown in Table 1.
[0094] (Resin synthesis example 5) The resin raw materials and solvent were DSDFBP 96.3g (0.228mol), DFBP 33.2g (0.152mol), TMBPF 97.4g (0.380mol), potassium carbonate 65.7g (0.475mol), DMSO 907.5g, and toluene 302.5g, and the same procedure as in Resin Synthesis Example 1 was repeated to obtain 173.6g of polymer powder (82% yield) (Resin 5). The results are shown in Table 1.
[0095] [Table 1]
[0096] [Example 1] Resin 1 produced in Resin Synthesis Example 1 was dissolved in DMF to prepare a varnish with a solids content of 10%.
[0097] Spray Coating A predetermined amount of this varnish was filled into a spray coating container, and the container was set on a spray gun (Wider 1, manufactured by Anest Iwata Corporation).
[0098] Next, a nonwoven fabric sheet made of polypropylene (Syntex (registered trademark) M03105 manufactured by Mitsui Chemicals, Inc.: air permeability measured by the A method (Fragile type method) described in JIS L 1096) of 5 cm 3 / cm 2 A nonwoven fabric sheet with a diameter of 1 / s and a thickness of 160 μm (both catalog values) was prepared as the substrate. The nitrogen gas pressure used for spraying was set to 0.3 MPa, and the varnish was sprayed onto the nonwoven fabric sheet from the tip of the spray nozzle by pressing the spray gun handle, so that the varnish was evenly applied to the sheet surface. It was dried at 80°C for 10 minutes, and nonwoven fabric laminate 1 was obtained.
[0099] The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3.
[0100] [Example 2] Resin 2 produced in Resin Synthesis Example 2 was dissolved in a DMF solvent to prepare a varnish with a solid content of 10%. This varnish was spray-coated onto a nonwoven fabric sheet in the same manner as in Example 1. It was dried at 80°C for 10 minutes to obtain a nonwoven fabric laminate 2. The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3.
[0101] [Example 3] Resin 3 produced in Resin Synthesis Example 3 was dissolved in a DMF solvent to prepare a varnish with a solid content of 10%. This varnish was spray-coated onto a nonwoven fabric sheet in the same manner as in Example 1. It was dried at 80°C for 10 minutes to obtain a nonwoven fabric laminate 3. The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3.
[0102] [Example 4] Resin 4 produced in Resin Synthesis Example 4 was dissolved in a DMF solvent to prepare a varnish with a solid content of 10%. This varnish was spray-coated onto a nonwoven fabric sheet in the same manner as in Example 1. It was dried at 80°C for 10 minutes to obtain nonwoven fabric laminate 4. The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3.
[0103] [Example 5] Resin 5 produced in Resin Synthesis Example 5 was dissolved in a DMF solvent to prepare a varnish with a solid content of 10%. This varnish was spray-coated onto a nonwoven fabric sheet in the same manner as in Example 1. The varnish was dried at 80°C for 10 minutes to obtain a nonwoven fabric laminate 5. The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3. The results of the sulfur atom content and sodium atom content of the cross section are shown in Table 4, and an SEM photograph of the coated surface is shown in FIG. 1, and an SEM photograph of the cross section is shown in FIG. 2.
[0104] It can be seen from Fig. 1 that the resin 5 is present on the surface of the nonwoven fabric fibers (including the case where the resin 5 surrounds the surface), and it can be seen from Fig. 2 that the nonwoven fabric has a laminated structure of a layer mainly composed of nonwoven fabric (corresponding to the base layer (LA)) and a layer in which the nonwoven fabric fibers and the resin 5 coexist (corresponding to the layer (LB)).
[0105] [Example 6] A polysulfone resin (Mw: about 22,000) manufactured by Sigma-Aldrich Japan LLC was used, which was dissolved in DMF to prepare a varnish with a solid content of 5%. The varnish was spray-coated onto a nonwoven fabric sheet in the same manner as in Example 1 (including the amount of resin applied). The varnish was dried at 80°C for 10 minutes to obtain a nonwoven fabric laminate 6. The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3.
[0106] [Comparative Example 1] The nonwoven fabric sheet made of polypropylene (Syntex (registered trademark) M03105, manufactured by Mitsui Chemicals, Inc.) used in the examples was used as is. The water permeation flux measurement results are shown in Table 2, and the fouling resistance evaluation results are shown in Table 3.
[0107] [Table 2]
[0108] As can be seen from the results in Table 2, the nonwoven fabric laminates of Examples 1 to 5 are laminates that exhibit water permeability, similar to Comparative Example 1. Therefore, it can be said that the nonwoven fabric laminates of Examples 1 to 5 are also self-evident nonwoven fabric laminates that have air permeability.
[0109] Although the reason why the water permeability differs in Examples 1 to 5 despite the same coating amount is not clear at present, it is presumed that the resin with a higher sulfonic acid group content prefers spreading over penetration into the nonwoven fabric, resulting in a thick coating around the fibers on the surface of the nonwoven fabric (see also FIG. 1). This shows that the polymer (B) of the present invention can ensure water permeability, and that the water permeability can also be adjusted by the structure of the resin to be coated.
[0110] [Table 3]
[0111] As shown in the results of Table 3, the nonwoven fabric laminates of Examples 1 to 5 show less protein adhesion than Comparative Example 1, and show high fouling resistance when used as a filter for an activated sludge phase. In addition, the relationship between the sulfonic acid group content and the albumin concentration may also be linear, but within this range of sulfonic acid group content, the influence of the amount of sulfonic acid groups is relatively small, and this may be a region where the effect is saturated.
[0112] [Table 4]
[0113] The results in Table 4 show that the nonwoven fabric laminate 5 has a laminate structure, since sulfur and sodium, which are believed to be derived from the polymer having sulfonic acid groups, were observed only on the coated surface. This is consistent with the SEM photograph in FIG. 2.
[0114] In addition, the SEM photograph in Figure 1 suggests that the nonwoven fabric has a porous structure in which a polymer having sulfonic acid groups is attached so as to cover the fibers, thereby ensuring breathability. [Explanation of symbols]
[0115] Layer-A Coated surface (Fig. 2) Layer-B Uncoated surface (Fig. 2) 1 Feed solution tank (Fig. 3) 2, 12 Channel (Fig. 3) 3, 13 Pump (Fig. 3) 4, 14 Balance (Fig. 3) 10 Evaluation device (Figure 3) 11 Draw solution tank (Fig. 3) 21 Evaluation cell (Figure 3) 22 Nonwoven fabric laminate sample (Figure 3) DS Draw Solution (Figure 3) FS Feed Solution (Figure 3)
Claims
1. The nonwoven fabric (A) includes a substrate layer (LA) and a layer (LB) including a polymer (B) having a sulfonic acid group structure, A nonwoven fabric laminate having the above-mentioned (LA) / (LB) structure and having air permeability.
2. 2. The nonwoven fabric laminate according to claim 1, wherein the polymer (B) is a polymer having a structural unit (1) represented by the following formula (1) and a structural unit (2) represented by the following formula (2). 【Chemistry 1】 [In formulas (1) and (2), R 1 ~R 10 are each independently H, Cl, F, or CF 3 Or C m H 2m+1 (m represents an integer of 1 to 10), R 1 ~R 10 may be present in two or more aromatic rings, and C m H 2m+1 If there are two or more C m H 2m+1 may be the same or different from each other. X 1 ~X 5 are each independently H, Cl, F, or CF 3 or a sulfonic acid group, X 1 ~X 5 at least one of the groups is a sulfonic acid group; X 1 ~X 5 may be present in two or more on an aromatic ring, and when two or more sulfonic acid groups are present on one aromatic ring, the respective sulfonic acid groups may be the same or different. A 1 ~A 6 each independently represents a direct bond, —CH 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, -O- or -CO-. i, j, k and l each independently represent 0 or 1.
3. 3. The nonwoven fabric laminate according to claim 2, wherein, in the entire polymer (B), the molar fraction of the structural unit (1) relative to the total amount of the structural unit (1) and the structural unit (2) is 0.1 to 0.
9.
4. 2. The nonwoven fabric laminate according to claim 1, wherein the polymer (B) has a weight average molecular weight (Mw) of 70,000 to 200,000.
5. 2. The nonwoven fabric laminate according to claim 1, wherein the polymer (B) has a sulfonic acid group equivalent of 200 to 5000 g / mol.
6. Water permeation flux (L / (m 2 The nonwoven laminate of claim 1, wherein h) (LMH)) is 100 to 100,000.
7. A method for producing the nonwoven fabric laminate according to any one of claims 1 to 6, comprising a step of applying a polymer (B) having a sulfonic acid group structure to at least one surface of a base material layer (LA) comprising a nonwoven fabric (A), and drying the applied polymer (B).
8. A membrane separation activated sludge treatment apparatus, comprising: a nonwoven fabric laminate according to any one of claims 1 to 6, which is immersed in a treatment water tank into which activated sludge containing microorganisms has been charged.
Citation Information
Patent Citations
Membrane washing method in membrane separation activated sludge method
JP2005074357A
Membrane separation type activated sludge treatment apparatus
JP2010253355A
Method for immersion-type washing of separation membrane device and system for immersion-type washing of separation membrane device
WO2011048681A1